2021
DOI: 10.2147/prbm.s339168
|View full text |Cite
|
Sign up to set email alerts
|

The Prevalence, Correlates and Functions of Non-Suicidal Self-Injury in Vietnamese Adolescents

Abstract: Purpose Research conducted across different countries has consistently identified non-suicidal self-injury (NSSI) to be a common and significant public health problem. This study examined the prevalence, associated factors and functions of NSSI, among a large sample of Vietnamese adolescents. Methods A total of 1316 high school students (15–18 years old, 63.3% female) across urban and suburban areas in Ho Chi Minh City, participated in this cross-sectional study. NSSI w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…Additionally, more females participated in our study than males and thus might lead to potential biases. Although gender differences in particiation in mental health studies have been commonly reported in Vietnam ( Thai, Vu & Bui, 2020 ; Thai et al, 2020 ; Thai et al, 2021 ), the reasons for this phenomenon and the magnitude of its effect on mental health and related factors warrant further investigations.…”
Section: Discussionmentioning
confidence: 93%
“…Additionally, more females participated in our study than males and thus might lead to potential biases. Although gender differences in particiation in mental health studies have been commonly reported in Vietnam ( Thai, Vu & Bui, 2020 ; Thai et al, 2020 ; Thai et al, 2021 ), the reasons for this phenomenon and the magnitude of its effect on mental health and related factors warrant further investigations.…”
Section: Discussionmentioning
confidence: 93%
“…Finally, 596 adolescents were included in the analysis. The inclusion criteria were as follows: adolescents 1) aged 11–18 years; 2) [ 36 ] assigned ICD-10 diagnostic codes for depression F32.0, F32.1, and F32.2: Essentials of Clinical Description and Diagnosis [ 37 ] (i.e., persistent depressed mood or decreased interest in activities for at least two weeks, accompanied by difficulty concentrating, feelings of worthlessness, excessive and inappropriate feelings of guilt and self-blame, and hopelessness); 3) who agreed to participate in the study voluntarily or whose legal guardian consented to their participation. The exclusion criteria were as follows: adolescents with 1) mental disorders other than depression, 2) a history of alcohol or drug abuse, 3) serious physical illness, 4) abnormal hearing or vision, 5) any suicidal intention or behaviors(e.g., jumping from heights, hanging oneself, consuming a lethal dose of drugs) during the period of self-injury, and 6) refusal to participate in the study.…”
Section: Methodsmentioning
confidence: 99%
“…NSSI behavior and function characteristics are often assessed by the functional assessment of self-mutilation questionnaire (FASM, 26), which has been demonstrated to possess good psychometric properties in both normal populations (27,28) and clinical samples (29) across various countries. Qu et al (13) translated and localized the scale and produced the Chinese version of FASM (C-FASM).…”
Section: Nssi Characteristicsmentioning
confidence: 99%